A Comparative Study of Printed vs. Dielectric Resonator Antennas for Ultra-Wideband Applications (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
This paper presents a comparative study of printed antennas and dielectric resonator antennas (DRAs) for ultra-wideband (UWB) applications. The work focuses on the design, simulation, and performance evaluation of both antenna types in terms of impedance bandwidth, radiation patterns, gain, and efficiency. The printed antenna offers advantages in terms of compactness and ease of fabrication, while the dielectric resonator antenna demonstrates superior radiation characteristics and higher efficiency. Through detailed parametric analysis and numerical simulations, the study highlights the trade-offs between size, bandwidth, and radiation performance, providing valuable insights for selecting suitable antenna types for various UWB communication systems. The results indicate that the choice between printed and dielectric resonator antennas depends on specific application requirements, such as compactness versus performance efficiency.